1995
DOI: 10.1111/j.1432-1033.1995.0931m.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Partial Characterization of the Erythrocyte Kx Protein Deficient in McLeod Patients

Abstract: A 37-kDa protein was immunopurified from human erythrocytes as a complex with a monoclonal antibody directed against the Kell blood group protein of 93 kDa. A rabbit antibody raised against the purified complex reacted on a Western blot with the 93-kDa and 37-kDa proteins and was able to immunoprecipitate the 37-kDa component from K0 erythrocytes which express large amount of the Kx antigen, but not from erythrocytes of patients suffering from McLeod syndrome, a X-linked disorder in which the Kx antigen is lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 19 publications
(10 reference statements)
2
32
0
Order By: Relevance
“…These results suggested that the active Xkr8 complex for the phospholipid scrambling is a tetramer consisting two caspasecleaved Xkr8 and two BSG or NPTN. Discussion XK, a member of the Xkr family, forms a complex with Kell, a type II membrane protein with metalloproteinase activity (25). XK connects to Kell via an S-S bond at the membrane-proximal regions (16).…”
Section: Effect Of Mouse Bsg and Nptn On Endogenous Xkr8-mediated Ptdsermentioning
confidence: 99%
“…These results suggested that the active Xkr8 complex for the phospholipid scrambling is a tetramer consisting two caspasecleaved Xkr8 and two BSG or NPTN. Discussion XK, a member of the Xkr family, forms a complex with Kell, a type II membrane protein with metalloproteinase activity (25). XK connects to Kell via an S-S bond at the membrane-proximal regions (16).…”
Section: Effect Of Mouse Bsg and Nptn On Endogenous Xkr8-mediated Ptdsermentioning
confidence: 99%
“…1). 1,2 Kell, an endothelin-3-converting enzyme, is a 93-kDa type II membrane glycoprotein that belongs to the M13 family of zinc endopeptidases. 3,4 Like other members of the M13 family, Kell has an intracellular N-terminal domain and a large extracellular C-terminal domain which contains a zinc-binding catalytic pentapeptide consensus sequence, HExxH (in Kell, HELLH).…”
Section: The Kell and Xk Proteinsmentioning
confidence: 99%
“…Biochemical studies in which Kell protein was isolated from red cells in nonreduced conditions, showed that Kell protein was associated with itself as an oligomer and was also complexed with other red cell membrane proteins (4). Later, immunoprecipitation of Kell protein in nonreduced conditions co-isolated XK, demonstrating that the two proteins exist as a disulfide-bonded complex on the red cell membrane (5). Further studies on the Kell-XK complex showed its absence in McLeod red cells and also demonstrated that although Ko (null) red cells have high Kx activity they contain less XK protein, indicating that lack of Kell protein may expose more Kx antigens on the cell surface (6).…”
mentioning
confidence: 99%
“…Positional cloning isolated the XK gene and predicted that it encodes a 444-amino acid protein that spans the red cell membrane 10 times and has structural characteristics of a membrane transporter (9). Since XK protein may only have one extracellular cysteine residue in the fifth extracellular loop, it was predicted that this residue may be involved in disulfide linkage with Kell protein, which has 15 extracellular cysteine residues and one cysteine in the transmembrane domain (5,10).…”
mentioning
confidence: 99%